The glypican Dally-like is required for Hedgehog signalling in the embryonic epidermis of Drosophila. - Desbordes, S.C.; Sanson, B. (Development, 2003)
The Drosophila genes dally and dally-like encode glypicans, which are heparan sulphate proteoglycans anchored to the cell membrane by a glycosylphosphatidylinositol link. Genetic studies have implicated Dally and Dally-like in Wingless signalling in embryos and imaginal discs. Here, we test the signalling properties of these molecules in the embryonic epidermis. We demonstrate that RNA interference silencing of dally-like, but not dally, gives a segment polarity phenotype identical to that of null mutations in wingless or hedgehog. Using heterologous expression in embryos, we uncoupled the Hedgehog and Wingless signalling pathways and found that Dally-like and Dally, separately or together, are not necessary for Wingless signalling. Dally-like, however, is strictly necessary for Hedgehog signal transduction. Epistatic experiments show that Dally-like is required for the reception of the Hedgehog signal, upstream or at the level of the Patched receptor.